1994
DOI: 10.1073/pnas.91.8.3215
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate regulates intracellular calcium and gene expression in oligodendrocyte progenitors through the activation of DL-alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors.

Abstract: Oligodendrocytes and their progenitors (0-2A) express functional kainate-and DL-a-amino-3-hydroxy-5-methyl-4-isoxazoleproplonlc acid (AMPA)-preferring glutamate receptors. The physiological consequences of activation of these receptors were studied In pified rat cortical 0-2A progenitors and In the primary oligodendrocyte cell line Changes in the mRNA levels of a set of immediate early genes were studied and were correlated to Intracellular Ca2+ concentration, as measured by fura-2 Ca+ imaging. Both in CG-4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 37 publications
9
91
0
Order By: Relevance
“…High expression of A-type K ϩ channels, ionotropic glutamate receptors from the AMPA type, and expression of the NG2 proteoglycan are characteristics of migrating and proliferating progenitor cells (Pende et al, 1994;Knutson et al, 1997;Wang et al, 2000;Diers-Fenger et al, 2001). We observed outwardly rectifying astrocytes in the ventral respiratory group and the hypoglossal nucleus of brainstem preparations, independent of their age.…”
Section: Putative Role Of Outwardly Rectifying Astrocytesmentioning
confidence: 70%
See 1 more Smart Citation
“…High expression of A-type K ϩ channels, ionotropic glutamate receptors from the AMPA type, and expression of the NG2 proteoglycan are characteristics of migrating and proliferating progenitor cells (Pende et al, 1994;Knutson et al, 1997;Wang et al, 2000;Diers-Fenger et al, 2001). We observed outwardly rectifying astrocytes in the ventral respiratory group and the hypoglossal nucleus of brainstem preparations, independent of their age.…”
Section: Putative Role Of Outwardly Rectifying Astrocytesmentioning
confidence: 70%
“…Concerted action of ionotropic glutamate receptor-mediated depolarization and outwardly rectifying, voltage-gated potassium channel activation was found to be involved in the gene regulation of glial progenitor cells (Pende et al, 1994). AMPA receptor and outward rectifier expression could therefore serve as a marker for immature, undifferentiated, or progenitor cells [but see Matthias et al (2003)].…”
Section: Presence Of Ampa-kainate Currentsmentioning
confidence: 99%
“…And lastly, kainate induces oligodendrocyte death at concentrations that mainly activate kainate-selective receptors (18,21). In addition to toxicity, previous findings indicated that kainate actions, such as the induction of early genes, in cells of the oligodendroglial lineage can be mediated by both AMPA and kainate receptors (22). Thus, it appears that activation of these two receptor classes may contribute to the same overall biological effects in oligodendroglial cells.…”
Section: Discussionmentioning
confidence: 94%
“…The depolarization caused by activated AMPA and kainate receptors may open Ca 2ϩ channels located in the vicinity of these receptors. Because of that, we examined whether blocking of Ca 2ϩ channels with nimodipine, at concentrations known to block all voltage-gated Ca 2ϩ channels in at least oligodendrocyte progenitors (22), had a protective effect on the viability of these cells. Indeed, we found that this blocker only partially reversed the toxicity induced by kainate application.…”
Section: Discussionmentioning
confidence: 99%
“…Although mRNA encoding the N-methyl-Daspartate (NMDA) type of glutamate receptor subunits can be also detected in oligodendroglia (Yoshioka et al, 1995), most studies suggest that these cells lack expression of functional NMDA receptors (Wyllie et al, 1991;Borges et al, 1994;Pende et al, 1994;Liu and Almazan, 1995). AMPA and kainate receptor expression is especially prominent in oligodendrocyte progenitor cells (Barres et al, 1990;Wyllie et al, 1991;Kastritsis and McCarthy, 1993;Holzwarth et al, 1994), and there are fewer descriptions of functional glutamate receptors in differentiated oligodendrocytes.…”
Section: Excitotoxicitymentioning
confidence: 99%